DEVELOPMENT OF ENVIRONMENT-BASED ISLAMIC COMIC LEARNING MEDIA AT CLASS IV IN ELEMENTARY SCHOOL - Nurul Hidayah; Nasir Nasir; Santy Afriana; Ayu Nur Shawmi (JIP Jurnal Ilmiah PGMI, 2021)
This research stems from the lack of variety of learning media in teaching and learning activities soit is necessary to develop interesting funny products in the form of comics as learning media. Thisresearch describes three items, the first is the development proses of environment-based Islamiccomic media. The second is expediency of environment-based Islamic comic media. The thirth isthe response of educator and student toward environment-based Islamic comic learning media inclass IV SD/MI. This research is a research and development study by ADDIE model whichincludes 5 steps, namely analysis, design, development, implementation evaluation. The productfeasibility test was conducted by several validators, namely 2 material experts, 2 media experts, 2linguists, 1 religious expert, 3 class IV teachers on class IV. The research results showed thatenvironmentl-based Islamic comic learning media gained an average percentage of material expertsat 93% with a very decent category, media experts got a score of 80% with a decent category,linguists got a score of 85% with a very decent category, ratings educators get an averagepercentage of 90.75% with a very decent category and the response of students get an averagepercentage of 96% with a very decent category. This shows that Islamic environment-based comicsthat have been developed are very suitable for use as learning media.